Prolonged CPR. (September 2016) - Vandervelden, Stefanie; Sabbe, Marc; Dewolf, Philippe
Abstract: Prolonged conventional cardiopulmonary resuscitation is still associated with low success rates and high variability in survival outcome. In order to avoid continuation of what might be futile life support we will outline in this article how to identify possible candidates for prolonged CPR taking into account outcome and prognostic parameters, origin of cardiac arrest and changing therapeutic strategies. We will focus on how high quality CPR can be delivered, discuss the value of several mechanical devices and techniques that have been developed to improve outcome of CPR and propose on how possible reversible causes of cardiac arrest can be recognised and treated early. Finally we will discuss the potential benefit of extracorporeal cardiopulmonary resuscitation. Highlights: Favorable neurological outcome depends mainly on quality and prolongation of CPR. Risk stratification and patient selection for prolonged CPR is of crucial importance. Early and high quality CPR with extended monitoring should be applied. Reversible causes should be diagnosed early. E-CPR can be used as a bridge to therapy.